A diagnostic evaluation model for complex research partnerships with community engagement: The partnership for Native American Cancer Prevention (NACP) model. (February 2015) - Trotter II, Robert T.; Laurila, Kelly; Alberts, David; Huenneke, Laura F.
Highlights: The article presents a diagnostic and intervention oriented evaluation model that is targeted at reducing the inordinately high failure rate of community–university partnerships directed at reducing health disparities in minority populations. The article combines classic logic model and query/theory based evaluation design with a systems dynamics and organizational network theory model for best practices in creating successful complex partnerships directed at reducing health disparities in minority populations. The article provides an evaluation model that is compatible with both community engaged program activities, and multiple PI cross-organizational program designs that often run into the Silo problem, the Not-In-My-Backyard problem, and the issues of significantly differing organizational cultures (goals, objectives, rewards, assumptions). Abstract: Complex community oriented health care prevention and intervention partnerships fail or only partially succeed at alarming rates. In light of the current rapid expansion of critically needed programs targeted at health disparities in minority populations, we have designed and are testing an "logic model plus" evaluation model that combines classic logic model and query based evaluation designs (CDC, NIH, Kellogg Foundation) with advances in community engaged designs derived from industry–university partnership models. These approaches support the application of a "near real time" feedback system (diagnosis and intervention) based on organizational theory, social network theory, and logic model metrics directed at partnership dynamics, combined with logic model metrics.